Кислотно-основное равновесие в смеси протофобного и протофильного полярных НДВС-растворителей: сольватация протона диметилсульфоксидом в ацетоне - Мчедлов-Петросян, Н.О.; Филатов, Д.Ю.; Гога, С.Т.; Лебедь, А.В. (Видавничий дім "Академперіодика" НАН України, 2008)
Acetone (AC) with additive of DMSO is proposed as a media for acid-base reactions, in which lyonium ion is the protonated protophilic co-solvent. The pKa values of picric acid in AC containing 0.5 to 6.0% (mol.) DMSO are treated in terms of the proton solvation by two DMSO molecules. In contrast with pure AC, the acid-base equilibria in the AC + DMSO mixture are insensitive to small water additives.